Primitivism and twentieth-century art : a documentary history - Flam, Flam; Deutch, Miriam; Neugroschel, Joachim (University of California Press, 2003)
Publisher's description: This book is the first to bring together texts documenting the encounter between Western artists and writers and what has historically been called primitive art--the traditional, indigenous arts of Africa, Oceania, and North America. Beginning with the "discovery" of that art by European artists and writers early in the twentieth century, this anthology charts the evolving pictorial